The Burden of Respiratory Viruses and Their Prevalence in Different Geographical Regions of India: 1970–2020 - Waghmode, Rushabh; Jadhav, Sushama; Nema, Vijay (Frontiers in Microbiology, 2021)
As per the 2019 report of the National Health Portal of India, 41,996,260 cases and 3,740 deaths from respiratory infections were recorded across India in 2018. India contributes to 18% of the global population, with severe acute respiratory infection (SARI) as one of the prominent causes of mortality in children >5 years of age. Measures in terms of the diagnosis and surveillance of respiratory infections are taken up globally to discover their circulating types, detect outbreaks, and estimate the disease burden. Similarly, the purpose of this review was to determine the prevalence of respiratory infections in various regions of India through published reports. Understanding the pattern and prevalence of various viral entities responsible for infections and outbreaks can help in designing better strategies to combat the problem. The associated pathogens comprise respiratory syncytial virus (RSV), rhinovirus, influenza virus, parainfluenza virus, adenovirus, etc. Identification of these respiratory viruses was not given high priority until now, but the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has sensitized our system to be alert about the burden of existing infections and to have proper checks for emerging ones. Most of the studies reported to date have worked on the influenza virus as a priority. However, the data describing the prevalence of other respiratory viruses with their seasonal pattern have significant epidemiological value. A comprehensive literature search was done to gather data from all geographical regions of India comprising all states of India from 1970 to 2020. The same has been compared with the global scenario and is being presented here.